2004
DOI: 10.1111/j.1365-277x.2004.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing to a self‐selected vegetarian diet on anthropometric measurements in UK adults

Abstract: The findings of our study suggest that significant dietary changes, helping people to conform more closely to current dietary recommendations, occurred when people became vegetarian. In this study we did not find any significant change in body weight, but significant reductions were observed in skinfold thickness and waist : height ratio which imply that on changing to a self-selected vegetarian diet, the subjects became leaner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
1
15
1
5
Order By: Relevance
“…Body mass index does not seem to change drastically after the adoption of a vegetarian diet, one longitudinal study with new vegetarians showed that there were no significant changes in the index, suggesting that the diet does not have a direct influence on body composition [20]. According to the BMI classification [21] there were no participants with overweight or obesity since the highest value found was 24.5.…”
Section: Discussionmentioning
confidence: 97%
“…Body mass index does not seem to change drastically after the adoption of a vegetarian diet, one longitudinal study with new vegetarians showed that there were no significant changes in the index, suggesting that the diet does not have a direct influence on body composition [20]. According to the BMI classification [21] there were no participants with overweight or obesity since the highest value found was 24.5.…”
Section: Discussionmentioning
confidence: 97%
“…The beneficial effects of calorie restriction on the gut microbiota including reduced levels of lipopolysaccharide-binding protein have also been demonstrated in rodents [110]. Vegetarian diet is rich in fiber and is commonly recommended as a component of lifestyle intervention to promote weight loss [111]. A recent study found that strict vegetarian diet ameliorates several abnormalities associated with metabolic diseases.…”
Section: Modulation Of Gut Microbiota In the Management Of Metabolic mentioning
confidence: 99%
“…10 Earlier work, by our group found that a vegetarian meal plan combined with a behavioral weight-counseling intervention led to weight loss and that those who followed the plan had not regained weight at 18 months. 11 Literature suggests that changing from a diet containing meat and fish to a vegetarian diet may result in reduced calorie and saturated-fat intake, an increase in energy from carbohydrates, resulting in a leaner body mass 12 and less weight regain. 13 While these findings are promising, they may have been partially attributable to a self-selection effect among those who adhered to the diet.…”
Section: Introductionmentioning
confidence: 99%